Is obesity a contraindication for simultaneous bilateral total knee arthroplasty? A prospective case–control study - Agarwala Sanjay; Wagh Yash Santosh; Vijayvargiya Mayank (SICOT-J, 2020)
Aim: Total Knee Arthroplasty (TKA) for decades has been an effective treatment modality for chronic arthritis of the knee. However, there is scarcity of literature comparing the functional outcomes of simultaneous bilateral TKA in obese patients with non-obese Indian population. We conducted this study to evaluate the functional outcomes and complication rates of simultaneous bilateral TKA in obese patients matched control with non-obese patients. Materials and methods: We divided the patients into two study groups based on their body mass index (BMI). Patients with a BMI of less than 30 were classified as non-obese and those with a BMI of more than 30 were classified as obese. All the patients underwent simultaneous bilateral TKA by a single surgeon using the same implant and technique. Patients were followed up regularly and functional outcomes in terms of Oxford knee score were noted at 6 weeks, 3 months, and 1 year. Post-operative complications and time to recovery was also compared. Results: Mean follow-up in obese group was 18 months (12–25 months) and in non-obese group was 17 months (12–24 months). Both the groups were matched with control in terms of pre-operative parameters. Post-operative hemoglobin drop, ICU requirement, length of hospital stay, mean walking time, and mean time to climbing stairs were similar in both the groups. Oxford knee score was significantly better in non-obese group at 6 weeks, but was similar in both the groups at 3 months, 6 months, 1 year, and last follow-up. There was no statistically significant difference seen in the complication rate in both the groups. There was no implant loosening or radiolucency seen. Conclusion: We conclude in our study that simultaneous bilateral TKA gives comparable mid-term results in obese patients in comparison to the non-obese patients.